Counselling self-efficacy as a mediator between computer self-efficacy and attitudes toward tele-mental health among school counsellors in Malaysia - Wei Rong Lee; Zaida Nor Zainudin; Engku Mardiah Engku Kamarudin (PLoS ONE, 2025)
Tele-mental health has become an effective method to offer mental health services to a diverse and geographically dispersed population such as Malaysia. The success of tele-mental health programs relies heavily on the willingness and readiness of counsellors to embrace technology in their practice. This highlights the significance of counsellor attitudes towards technology in executing such initiatives. This study investigates how counselling self-efficacy mediates the relationship between computer self-efficacy and attitudes toward tele-mental health among Malaysian school counsellors. A cross-sectional study was conducted involving 348 school counsellors randomly selected from two states in Malaysia. The participants completed three instruments to evaluate their counselling self-efficacy, computer self-efficacy, and attitudes towards tele-mental health. Correlation results showed significant positive relationships among all three variables. Mediation analysis using PROCESS Macro (Model 4) demonstrated that counselling self-efficacy partially mediated the relationship between computer self-efficacy and attitudes toward tele-mental health (β = .030, 95% CI [.003,.067], t = 2.75, p < .01). The direct effect remained significant (β = .122, p < .01), confirming partial mediation. These findings suggest that improving school counsellors’ confidence in technological and counselling skills may potentially improve favorable attitudes towards tele-mental health adoption. This study contributes to the counselling profession in preparing school counselors for delivery tele-mental health and supporting the integration of technological training in counselling development programs.